Malay food language and terminologies: young Malay culinarians’ understanding and usage / Khairunnisa Mohamad Abdullah - Mohamad Abdullah, Khairunnisa (2012)
Malays as Malaysia indigenous group is having vast and valuable food terminologies which represent one of the language aspect that should be preserved. Those terminologies not only associated to varieties of food names but also to different kinds of ingredients, equipments, cooking methods and food preparations. However, although Malay culinary is very rich in terminologies, much of the terminologies are no longer being learned not only among the ordinary youngsters but also among the young professional chefs and culinarians. Many of Malay food terminologies are failing out of use and being replaced by others foreign language such as English and French that they learn from their culinary studies. Owing to the lack of usage, much of the Malay foods terminologies are believed getting ignored and gradually disappeared and in fact some of the words do no longer exist. Therefore, this study empirically investigates the level of understanding of Malay food terminologies pertaining to Malay food preparations, cooking methods and food names terminologies and its impact to the usage among the young Malay culinarians in their daily cooking activities. A quantitative approach was used in getting information from the targeted respondents. The results from descriptive and multiple regression analyses revealed that the majority of the respondents have a relatively low understanding on Malay food terminologies including the food preparation, cooking methods and food names terminologies. The finding also proved that the respondents only use a few Malay food terminologies in their daily cooking activities. Therefore, understanding and usage of Malay food terminologies are critically important especially among the young generation to ensure the terminologies are being preserved and continuously being use in the future.